2022
DOI: 10.1093/mnras/stac969
|View full text |Cite|
|
Sign up to set email alerts
|

Fundamental scales in the kinematic phase of the turbulent dynamo

Abstract: The turbulent dynamo is a powerful mechanism that converts turbulent kinetic energy to magnetic energy. A key question regarding the magnetic field amplification by turbulence, is, on what scale, kp, do magnetic fields become most concentrated? There has been some disagreement about whether kp is controlled by the viscous scale, kν (where turbulent kinetic energy dissipates), or the resistive scale, kη (where magnetic fields dissipate). Here we use direct numerical simulations of magnetohydrodynamic turbulence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 83 publications
0
11
2
Order By: Relevance
“…We do not explicitly include viscosity in our model, instead, the viscosity is due to numerical dissipation (see Benzi et al 2008;Federrath et al 2011, for a discussion). The numerical viscous scale in our simulations is expected to be around 0.6 kpc, roughly at 15Δ𝑥 (where Δ𝑥 is the numerical cell size), which we obtain from fitting the power spectrum model in Kriel et al (2022) to our velocity power spectrum. For the hot ICM, we compare the numerical viscosity with the Spitzer viscosity values from Spitzer (1962) and find it to be suppressed by a factor of ∼ 600.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…We do not explicitly include viscosity in our model, instead, the viscosity is due to numerical dissipation (see Benzi et al 2008;Federrath et al 2011, for a discussion). The numerical viscous scale in our simulations is expected to be around 0.6 kpc, roughly at 15Δ𝑥 (where Δ𝑥 is the numerical cell size), which we obtain from fitting the power spectrum model in Kriel et al (2022) to our velocity power spectrum. For the hot ICM, we compare the numerical viscosity with the Spitzer viscosity values from Spitzer (1962) and find it to be suppressed by a factor of ∼ 600.…”
Section: Methodsmentioning
confidence: 85%
“…They also find that turbulent gas motions are predominantly solenoidal, although the driving is mainly compressive (through inner and merger shocks), similar to our results in section 3.6. Seta & Federrath (2022) study the effect of the driving parameter on the turbulent dynamo in the two-phase ISM. Similar to our study, they find 𝐹 baro to generate seeds of enstrophy in their compressive driving run at initial times.…”
Section: Comparison With Recent Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of characteristic length scales in a small-scale dynamo continued attracting attention and has been investigated in more detail by Cho & Ryu (2009) with applications to the intergalactic medium. More recently, Kriel et al (2022) confirmed the Pr −1/2 M scaling for 1 ≤ Pr M ≤ 260 also for the kinematic phase of the dynamo. The small-scale properties of interstellar turbulence can be assessed through interstellar scintillation measurements of pulsars (Cordes et al 1985;Rickett 1990;Armstrong et al 1995;Bhat et al 2004;Scalo & Elmegreen 2004).…”
Section: Introductionmentioning
confidence: 67%